ANALYSIS OF ASSOCIATION BETWEEN THE DENSITY OF INFILTRATION IN PRIMARY CARCINOMA OF THE MAMMARY GLAND BY TUMOR-ASSOCIATED MACROPHAGES AND POSTOPERATIVE PROGNOSIS - A.Z. Aikian; V.I. Shynkevych; I.P. Kaidashev (Проблеми екології та медицини)
Tumor-associated macrophages (TAM) of the M2-type dominate in tumors and produce molecules, favorable for their growth, stimulating tumor growth. However, changing the M2-type for M1 can slow down or arrest this growth. For realization of the M1 / M2 modulation direction in the treatment of carcinoma / breast cancer (BC), a substantiated diagnosis and confirmation of the TAM negative prognosis is necessary. Therefore, the aim of the study was to evaluate the relation of tumor associated macrophages to the postoperative prognosis / survival of patients with 5 molecular-biological types of breast carcinoma. Materials of the study were intraoperative tissues of tumors and ipsilateral lymph nodes in radically removed mammary glands. Pathomorphological study of lymph nodes was conducted to clarify the diagnosis in relation to N0/1. The density of TAM infiltration was determined by immunohistochemical staining of CD68 and CD163 in 30 samples of five molecular biological types of breast cancer (three clinical cases of each type). Immunohistochemical (IHC) studies for the determination of TAM and M2-like macrophages were conducted using streptavidin-peroxidase method. The quantitative representation of CD68 + and CD163 + Mph is very different from patient to patient and also within one sample, which depends, in particular, on the morphological characteristics of breast cancer, studied by the biopsy. The density of infiltration by CD163 + macrophages of the BC focus negatively correlated with postoperative survival, which did not reach statistical significance, but is included in the general concept of a negative prognosis of infiltration by M2-like macrophages. Further research is needed to confirm the negative significance of the ТАМ infiltration density in the BC primary focus for postoperative prognosis. Promising is the development of differential diagnosis and approach to the treatment of breast cancer, taking into account the levels of its infiltration by subpopulations of TAM.